(3GdPQjYI Gdj ecGQe GdTQjYIs - (3CHh GdbGSe GdQGZH GdGUHgGfjs
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI bGd CHh GdbGSe GdQGZH cfJ bO GTQJ ajgG GedjJg ef cJGH JMbjb GdHjGf aj JChjd GdbQBf Gdj GdaQb Hjf GMcGe GdTQjYI hecGQegG s
(3BNQgG (B:s
(3hUMJc bHd Sbec haQGZc bHd TZdc hZfGc bHd abQc hMjGJc bHd ehJc s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GjGUhajG (B(2898) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs